Flood Hazard Analysis and Adaptive Mitigation in Coastal Semarang Using a Geographic Information System Approach - Alif Lombardoaji Sidiq; Muhammad Farhan Rizqi; Fredi Dwi Purnama; Pipit Skriptianata Putra Pranida (Greenation International Journal of Engineering Science, 2026)
The coastal area of Semarang City is divided administratively based on sub-districts of Tugu‚ West Semarang‚ East Semarang‚ North Semarang‚ and Genuk․ The area is highly vulnerable to inundation and wide-ranging flooding due to excess rainfall‚ low elevation‚ and hydrological impacts caused by reclamation activities in the city of Semarang․ The aim of this study was to spatially identify this hazard and suggest appropriate mitigation strategies‚ based on a four-factor quantitative GIS model․ The factors used were slope‚ average annual rainfall‚ land use and soil type․ The four were combined using overlay and weighting․ The resulting model revealed that 5‚364․45 hectares (66․40%) of the study area is Highly Vulnerable․ Another 33․26% (2‚687․42 hectares) was determined to be Moderately Vulnerable and 0․33% (27․07 hectares) Slightly Vulnerable․ No land was determined to be completely safe․ In light of this distribution‚ the recommendations made here are weighted towards structural measures (where risk is highest)‚ such as hardening the seawalls and normalizing the polder system․ It will lower the risk of future disasters in the long run․